IMPLEMENTASI KEPEMIMPINAN KEPALA SEKOLAH DALAM PELAKSANAAN MANAJEMEN BERBASIS SEKOLAH DI SEKOLAH DASAR - Anak Agung Gede Agung; Chindytia; Ni Luh Putu Suryani; Ni Made Catrie Prapinta; Sagung Wina Anggreni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the implementation of school principal leadership in School-Based Management (SBM) at SDN 18 Sesetan, South Denpasar District, Denpasar City, Bali. The research employs a qualitative descriptive approach using a case study method. Data were collected through in-depth interviews with the key informant Dra. Anik Poedjiastoeti, M.Pd. (Principal of SDN 18 Sesetan), field observations, and document analysis. Findings reveal that SDN 18 Sesetan possesses a primary strength in its human resources, with all 12 teachers certified and capable of integrating technology into instruction. The principal demonstrates participative and transformational leadership styles, evidenced by effective collaboration between teachers and the school committee. SBM implementation is effective in human resource management and community relations, yet faces serious challenges in infrastructure management due to limited operational funding. The study recommends funding diversification, mid-term infrastructure development planning, and strengthened partnerships with the local education office and private sector.